Accuracy of common proton density fat fraction thresholds for magnitude- and complex-based chemical shift-encoded MRI for assessing hepatic steatosis in patients with obesity. - Cunha, Guilherme Moura; Thai, Tydus T.; Hamilton, Gavin; Covarrubias, Yesenia; Schlein, Alexandra; Middleton, Michael S.; Wiens, Curtis N.; McMillan, Alan; Agni, Rashmi; Funk, Luke M.; Campos, Guilherme M.; Horgan, Santiago; et al. (Abdominal Radiology, 2020)
Purpose: MRI proton density fat fraction (PDFF) can be calculated using magnitude (MRI-M) or complex (MRI-C) MRI data. The purpose of this study was to identify, assess, and compare the accuracy of common PDFF thresholds for MRI-M and MRI-C for assessing hepatic steatosis in patients with obesity, using histology as reference. Methods: This two-center prospective study included patients undergoing MRI-C- and MRI-M-PDFF estimations within 3 days before weight loss surgery. Liver biopsy was performed, and histology-determined steatosis grades were used as reference standard. Using receiver operating characteristics (ROC) analysis on data pooled from both methods, single common thresholds for diagnosing and differentiating none or mild (0–1) from moderate to severe steatosis (2–3) were selected as the ones achieving the highest sensitivity while providing at least 90% specificity. Selection methods were cross-validated. Performances were compared using McNemar's tests. Results: Of 81 included patients, 54 (67%) had steatosis. The common PDFF threshold for diagnosing steatosis was 5.4%, which provided a cross-validated 0.88 (95% CI 0.77–0.95) sensitivity and 0.92 (0.75–0.99) specificity for MRI-M and 0.87 sensitivity (0.75–0.94) with 0.81 (0.61–0.93) specificity for MRI-C. The common PDFF threshold to differentiate steatosis grades 0–1 from 2 to 3 was 14.7%, which provided cross-validated 0.86 (95% CI 0.59–0.98) sensitivity and 0.95 (0.87–0.99) specificity for MRI-M and 0.93 sensitivity (0.68–0.99) with 0.97(0.89–0.99) specificity for MRI-C. Conclusion: If independently validated, diagnostic thresholds of 5.4% and 14.7% could be adopted for both techniques for detecting and differentiating none to mild from moderate to severe steatosis, respectively, with high diagnostic accuracy.